From Friendly to Flirty: A Semantic Pejoration of The Word 'Friendly'in Indonesian Social Media - Maulinda Dwi Mawardani; Badri Badri (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
This study examines the phenomenon of semantic pejoration of the English word 'friendly' in Indonesian social media discourse. Denotatively, 'friendly' means 'ramah' (approachable/kind) and carries a positive connotation; however, in its actual usage on platforms such as Instagram and TikTok, the word has undergone significant semantic shift and is now frequently associated with flirtatious, unfaithful, or sasimo behavior. This study employs a descriptive qualitative approach, with data consisting of comments and content from social media collected through purposive sampling during the period of 2022–2026. A total of 18 data points were analyzed using the theory of pejorative semantic change. The results indicate that the word 'friendly' has undergone pejoration triggered by interpersonal and romantic relationship contexts, reinforced by the dynamics of Indonesian Gen Z digital communities. The study also notes the emergence of a semantic correction phenomenon toward the end of the research period, wherein some users have begun to restore the word's original positive meaning.